A study on serum vitamin B12 levels in type 2 diabetic women and its correlation with metformin therapy - L. S., Yashaswini (International Journal of Medical Research and Review, 2019)
Background: Diabetes Mellitus (DM) is a major emerging health issue and the risk factors are varied in women making them susceptible to it. Metformin is most preferred and widely used drug worldwide due to various reasons. Vitamin B12 deficiency in DM caused by Metformin is least known side effect. Objective: This study was taken up to assess the correlation between deficiency and duration and dose of metformin treatment. Methods: This being a hospital based observational study, 650 Diabetic women were evaluated by detailed questionnaire, general physical examination, fasting blood glucose (FBS), post prandial blood glucose (PPBS), serum Vitamin B12 levels, CBC and NCS. Results: The mean age of the cases was 51.98±5.17years. 164/408 cases (on metformin therapy for >3 months) had low vitamin B12 as against 22/242 controls (never on metformin therapy). Mean Serum vitamin B12 was low in cases with less duration of DM when compared to cases with longer duration. Vitamin B12 deficiency was correlated with anemia and neuropathy. Conclusions: Metformin treatment in cases is associated with higher prevalence of Vitamin B12 deficiency which increases with duration of DM and dose of metformin. Deficiency correlated with development of macrocytic anemia and worsening of neuropathy. In some, symptoms of deficiency are difficult to diagnose and can be irreversible if left untreated (like neuropathy). Routine screening of Vitamin B12 levels, CBC, NCS should be done in all diabetic women at the beginning of metformin therapy, and yearly thereafter. Treatment and prevention of deficiency is easy, cheap, safe, and effective.